Transforming Data to Decisions: AI-Driven Smart Governance and Digital literacy in India’s Public Policy Ecosystem (Journal of Informatics Education and Research, 2025)
This article discusses how Data Science and artificial intelligence (AI) are redefining public policy architecture in India. It looks at how technologies such as real-time analytics, predictive modelling, and adaptive decision-making are being integrated into governance by initiatives such as the India AI Mission, Digital India, and the National Data and Analytics Platform. These programs mark a substantial shift towards evidence-based policymaking, in which huge amount of data are used not just to improve the quality of services but also to forecast demand from the public and assess the actual impact of policy decisions.  The paper focuses on how AI applications are influencing and shaping major sectors. In sector like healthcare, AI facilitates early disease detection and online diagnosis in remote areas. In field of education, data-intensive analysis helps in the identification of students who are prone of drop- out and also in the development of personalized learning programs. The agricultural sector benefits from the use of satellite imagery and machine learning to manage crop cycles and reduce climate-related hazards. Simultaneously, in urban areas, government employs modern data technologies to improve traffic management, public safety, and environmental monitoring. While these developments show the potential of digital governance, the article emphasizes the significance of ethical and legal safeguards. The implementation of the Digital Personal Data Protection Act (DPDPA 2023) is an important step toward tackling data privacy, algorithmic unfairness, and uneven access to digital infrastructure. Without rigorous regulation and inclusion, the technologies that empower citizens may exacerbate existing inequalities.